Diagnóstico de la comunicación interna en la empresa Cinemark mall de los Andes Ambato, año 2013. - Galarza Mayorga, Paula Gioconda (2014)
All businesses regardless of the activity they are engaged, have an internal communication system through which information flows, the system in most cases occur informally, without planning or control, so that presents the need to evaluate, in this case a company dedicated to entertainment where communication is vital. Like a doctor makes a diagnosis to know what disease the patient has, in this case of study is also performed using a diagnostic tool that provides the research method for the study of social problems. This diagnosis allows, evaluate and determine the status of the communication from the company, make the communication system used in the organization, recognize the weaknesses that should be improved and establish a proposal which is applied in the right way would be helpful for the company and their members.